The effect of juggling on the proprioceptive and attentional abilities among older women - Malik, Jakub; Główka, Natalia; Jelonek, Wojciech; Maciaszek, Janusz (Frontiers in Public Health, 2024)
Background: A decrease in awareness of body segments in space can be affected by age-related changes in attentional abilities. However studies have reported that physical activity can improve proprioception among older adults, but proven forms of activity that have such potential are rare. Juggling seems to be a promising form of activity for proprioception, as it requires both high attention and high sensory accuracy. The first hypothesis assumed that the juggling intervention had a positive impact on the ability of the ipsilateral and contralateral position matching of the elbow joint without visual input, whereas the second hypothesis assumed that there would be a correlation between cognitive abilities and the efficiency of the joint position sense. Methods: Twenty older women (69.95±4.58) participated in a study based on repeated measures with a Latin square design. Measurements were performed at three time points (TPs; baseline, juggling, control). Ipsilateral and contralateral elbow joint position matchings without visual or verbal feedback of accuracy were used for the proprioception assessment. Vienna Test System protocols for attention and reaction time variables were used. Results: Although significant changes occurred between the baseline and other TPs measurements of joint position sense accuracy, a juggling effect was not observed. Low and medium correlations of the decision time and the variability of choice reaction time on the accuracy were observed for contralateral accuracy. For ipsilateral accuracy, a relationship was observed only with handedness. Attention test scores did not correlate with joint position sense accuracy. Conclusions: The effect of juggling on changes in position matching ability has not been shown. Cognitive abilities, like decision speed and stability of choice reaction time, may contribute to more accurate position matching among older women. Trial registration: The study was registered retrospectively at ClinicalTrials.gov (NCT06108713).